Financial contagion and the role of the central bank - Castiglionesi, Fabio (Journal of Banking & Finance, 2007)
We investigate the role of a central bank (CB) in preventing and avoiding financial contagion. The CB, by imposing reserve requirements on the banking system, trades off the cost of reducing the resources available for long-term investment with the benefit of raising liquidity to face an adverse shock that could cause contagious crises. We argue that contagion is not due to the structure of the interbank deposit market, but to the impossibility to sign contracts contingent on unforeseen contingencies. As long as incomplete contracts are present, the CB may have a useful role in curbing contagion. Moreover, the CB allows the banking system to reach first-best allocation in all the states of the world when the notion of incentive-efficiency is considered. If the analysis is restricted to constrained-efficiency, the CB still avoids contagion without, however, reaching first-best consumption allocation. The model provides a rationale for reserve requirements without the presence of fiat money or asymmetric information.